Features of the metabolic syndrome and subclinical atherosclerosis in patients with cerebrotendinous xanthomatosis: An augmented risk for premature cardiovascular disease - Cohen, H.; Hassin-Baer, S.; Shaish, A. (Frontiers in Genetics, 2022)
Background: Cerebrotendinous xanthomatosis (CTX) is a rare lipid storage disease, caused by deficiency of sterol-27-hydroxylase. Xanthomatous lesions in numerous tissues, and an elevation of cholestanol levels, characterize the disease. Its natural course is progressive neurologic deterioration, leading to premature death. Chronic treatment with oral chenodeoxycholic acid (CDCA) reduces cholestanol levels. Occurrence of premature atherosclerosis has been described in CTX in an unknown mechanism. Aim: The aim of the current work was to evaluate the potential metabolic abnormalities and preclinical vascular changes in Israeli CTX patients. Methods: Ten subjects with CTX were studied. Features of the metabolic syndrome were evaluated and carotid intima media thickness (cIMT) was measured in the common carotid arteries. Results: All patients were diagnosed with CTX, and all received treatment with CDCA, which resulted in normalization of their plasma cholestanol levels. At the conclusion of the follow up, risk factors for CVD and features of MS were present in all the patients and in three patients, cIMT was significantly higher compared to control subjects. Conclusion: Cardiovascular risk factors and premature vascular changes exist in young CTX patients and proper assessment should be implemented with preventive measures to reduce the risk of atherosclerotic cardiovascular disease in CTX patients.